Performance of solar adsorption refrigeration in system of SAPO-34 and ZSM-5 zeolite. (15th November 2016) - Du, S.W.; Li, X.H.; Yuan, Z.X.; Du, C.X.; Wang, W.C.; Liu, Z.B.
Highlights: The novel adsorption refrigeration system with a solar-tracking parabolic trough was developed. The heat and mass transfer characteristic of ZSM-5 and SAPO-34 was examined. The mass transfer of the SAPO-34 was better while the heat transfer of the ZSM-5 zeolite was better. SAPO-34 zeolite was of higher desorption speed. The refrigeration capacity of the SAPO-34 was superior to that of the ZSM-5. Abstract: Under the solar heating condition a novel adsorption refrigeration system is developed and tested practically. The adsorption bed of the system is reformed from the solar evacuated glass tube, to which a solar-tracking parabolic trough has been specially designed. With the water vapor as the refrigerant medium, the heat and mass transfer performance of the ZSM-5 and SAPO-34 zeolite in the adsorption/desorption process was studied. The air cooling mode and the water cooling mode were applied to check the effect on the adsorption system. The experimental results showed that the mass transfer of the SAPO-34 was better while the heat transfer of the ZSM-5 zeolite was better. Under the same heating condition, the SAPO-34 zeolite was of higher desorption speed and more easily to reach to the equilibrium state. In general, the refrigeration capacity of the SAPO-34 is superior to that of the ZSM-5 and is more suitable to apply in the solar adsorption refrigeration.